PENGARUH BRAND EXTENSION DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN ENDURO MATIC-G MELALUI CITRA MEREK (Survey Pada Konsumen Pengguna Enduro Matic-G di Kota Serang) - Sulaiman, Agus; Surya, Djasuro; Kamsin, Daenulhay (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2018)
New product marketing through brand extension strategies that are supported by product quality which said to be successful if the extension products are acceptable and make better consumer decisions. This study aims to determine the direct or indirect influence of brand extension and product quality on customer purchasing decisions through brand image Enduro Matic G. Research using survey method conducted on 110 customers Enduro Matic G in Serang City. Data analysis using Structural Equation Model of Partial Least Square (SEM PLS) with the result of research obtained 1) brand extension have a positive and significant effect on purchasing decision; 2) product quality has a positive and significant effect on purchasing decision; 3) brand extension has no effect on brand image; 4) product quality has a positive and significant effect on brand image and 5) brand image has no effect on customer purchasing decision of Enduro Matic-G. Brand extensions and good product quality are proven to make better customer purchasing decisions, but can not make the Enduro Matic G brand image better in the eyes of its customers.